THERE IS NO ASSOCIATION BETWEEN SYSTOLIC BLOOD PRESSURE AND MORTALITY IN HEAD TRAUMA PATIENTS - Akhmad Renaldi Renaldi; Rismia Agustina; Oski Illiandri (Indonesian Journal for Health Sciences, 2019)
Head trauma is a major public health problem and is a major cause of mortality worldwide. In the case of head trauma patients, the mortality is determined by using systolic blood pressure as one of the predictors. This research aims to identify the association between systolic blood pressure and mortality in head trauma patients at Ulin Hospital, Banjarmasin. As a method, nonprobability sampling was used with accidental sampling technique and thirty-eight head trauma patients come to the AE of Ulin Hospital. The observation sheet was used to record the initial systolic blood pressure measurements as well as the assessment of mortality in head trauma patients within twenty-four hours to find out whether the patient had mortality or not. Based on the data analysis, it showed that there is no association between systolic blood pressure and mortality in head trauma patients at Ulin Hospital. Other risk factors may cause mortality in head trauma patients.